Nanotechnology in Asia: A preliminary assessment of the existing legal framework - Karim, M.E. (Korea Legislation Research Institute, 2014)

(untitled)
Nanotechnology, often referred to as the next industrial revolution after internet, is an interdisciplinary study with limitless potential. It is claimed that nanotechnology is now at the stage where ICT and use of plastic were in 1960s and biotechnology was in 1980s. Already more than 2000 nano-enabled consumer products are in the market and the ILO predicts that by 2020, twenty percent of the products will be developed using nanotechnology. The UNESCO traced top ten applications of nanotechnology within the UN Millennium Development Goals (MDGs), which are: (a) Energy storage, productions and conversion; (b) Agricultural productivity enhancement; (c) Water treatment and remediation; (d) Disease diagnosis and screening; (e) Drug delivery systems; (f) Food processing and storage; (g) Air pollution and remediation; (h) Construction; (i) Health monitoring; and (j) Vector and pest detection and control. With all these promises, concerns are also there, as a majority of the researchers feel that nanoparticles must have some adverse health and environmental effects. Besides, to many organizations, nanotechnology is the next asbestos. However, it is a matter of great concern that there is no specific internationally agreed legal framework to deal with nanotechnology. The mistake for which the introductions of genetically modified food or nuclear energy could not be completely successful, should not be repeated and the application of nanotechnology should be encouraged within the approved legal framework. Some of the Asian countries like China, Japan, South Korea, Malaysia, Singapore, India, Taiwan and few others have already achieved tremendous success in this area. This paper aims at introducing the legal aspects of nanotechnology and its regulatory developments in some of the Asian countries. The consideration of most of the available literature in this area being mainly from Europe and North America, this paper aims to share the legal development of nanotechnology in the Asian context.